The Effect of Moldboard Plowing Speed on The Physical Properties of The Topsoil and Subsoil layers - Dheyaa S. Ashour; Hussain A. Safi; Ahmad A. Al-Mothefer (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
The soil compaction of moldboard plowing appears as a plow pan, which causes many problems such as resisting root growth, lowering drainage and degrading of soil structure. This study was carried out to determine the effect of surface tillage via using the moldboard plow of 30 cm depth under three operational speeds {S1=0.49, S2 =0.74, and S3 =1.05 m.s-1} on the soil bulk density ( ), total porosity (f) and penetration resistance (P.R). Soil property of three depths with intervals 10 cm were measured for two positions: {topsoil depth (Td) which represent 0-10, 10-20, and 20-30 cm and subsoil depth (Sd) which represent 30-40, 40-50 and 50-60 cm}. The study results indicated that the lowest values for  (0.86 and 0.69 Mg.m-3) and P.R (983.61 and 118.44 kN.m-2), and the highest values for f (67.52% and 74.05%), were recorded under the treatments of S3, and Td, respectively. The soil depth has a significant effect on the P.R only; the D1 reached the lowest value (861.47 kN.m-2). The overlapping of S3×Td has recorded the lowest values for  (0.51 Mg.m-3) and P.R (106.42 kN.m-2) and the highest value for f (80.82%). The moldboard plow disturbed the topsoil aggregates so that the Td was more homogeneous forces (no significant differences between its depths). However, the weights of the soil depths of 0-10, 10-20, 20-30, 30-40 and 40-50 cm were accumulate on the (50-60cm) which get the highest value of  (1.34 Mg.m-3) and P.R (2561.78 kN.m-2), and the lowest value of f (49.46%). The triple interaction was significant with regard to  and f only. The treatment S3TdD3 recorded the lowest value for  (66.67%) and the highest value for f (82.48%) compared the treatment of S2SdD3, which reached the highest  and the lowest f.